Answer:
[tex]p(1) - p(-1) =8[/tex]
Step-by-step explanation:
Given
[tex]p(m) = 4m^3 + 3[/tex]
Required
[tex]p(1) - p(-1)[/tex]
First, we calculate p(1)
Substitute 1 for m in [tex]p(m) = 4m^3 + 3[/tex]
[tex]p(1) = 4(1)^3 + 3[/tex]
[tex]p(1) = 4*1 + 3[/tex]
[tex]p(1) = 4 + 3[/tex]
[tex]p(1) = 7[/tex]
Next, we calculate p(-1)
Substitute -1 for m in [tex]p(m) = 4m^3 + 3[/tex]
[tex]p(-1) = 4(-1)^3 + 3[/tex]
[tex]p(-1) = 4*-1 + 3[/tex]
[tex]p(-1) = -4 + 3[/tex]
[tex]p(-1) = -1[/tex]
[tex]p(1) - p(-1)[/tex] is then calculated as:
[tex]p(1) - p(-1) = 7 - (-1)[/tex]
[tex]p(1) - p(-1) = 7+1[/tex]
[tex]p(1) - p(-1) =8[/tex]